1984
DOI: 10.1002/eqe.4290120109
|View full text |Cite
|
Sign up to set email alerts
|

Modal decomposition method for stationary response of non‐classically damped systems

Abstract: SUMMARYThe stationary response of multi-degree-of-freedom non-classically damped linear systems subjected to stationary input excitation is studied. A modal decomposition procedure based on the complex eigenvectors and eigenvalues of the system is used to derive general expressions for the spectral moments of response. These expressions are in terms of cross-modal spectral moments and explicitly account for the correlation between modal responses; thus, they are applicable to structures characterized with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(53 citation statements)
references
References 5 publications
(1 reference statement)
3
50
0
Order By: Relevance
“…The mean peak story drifts of the building with T-EIMDs subjected to the given design displacement spectrum S D (ω; h) can be evaluated by the expanded CQC method (Igusa et al, 1984;Yang et al, 1990) by…”
Section: Modal Analysis Of Structures With T-eimdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean peak story drifts of the building with T-EIMDs subjected to the given design displacement spectrum S D (ω; h) can be evaluated by the expanded CQC method (Igusa et al, 1984;Yang et al, 1990) by…”
Section: Modal Analysis Of Structures With T-eimdsmentioning
confidence: 99%
“…The developed method utilizes the expanded complete quadratic combination (CQC) method, which is a modal analysis method based on the complex eigenvalue analysis of a structure with nonproportional damping (Igusa et al, 1984;Yang et al, 1990). It is found that the proposed procedure can find the necessary storywise distribution of the T-EIMDs' inertial masses in a multistory building.…”
Section: Introductionmentioning
confidence: 99%
“…Igusa et al [10] provide the cross-spectral moments λ l,mn for response to the white-noise input G 0 . Introducing the modal correlation coefficients …”
Section: Response Prediction Formula Considering Overdamped Modesmentioning
confidence: 99%
“…The derived formula is extended from a response spectrum method for a non-classically damped system proposed by Igusa et al [10] and Zhou et al [11] considering overdamped modes, and is expressed in a simpler and more uniform form than that proposed by Song et al [12]. The estimation accuracy is then examined by comparing the results of a time-history analysis using a mid-storey-isolated building model.…”
Section: Introductionmentioning
confidence: 99%
“…The constraints are mostly imposed on the interstory drifts of a structure subjected to a specified earthquake input, since the interstory drifts can be regarded as the most important seismic design index. The mean peak interstory drifts of the building installed with dampers subjected to the specified design displacement response spectrum can be estimated using the expanded complete quadratic combination (CQC) method, which entails modal analysis with complex eigenvalue analysis (Igusa et al, 1984;Yang et al, 1990).…”
Section: Introductionmentioning
confidence: 99%